Scientific man vs. power politics - Morgenthau, Hans J. (The University of Chicago press, 1946)
This book introduce the dilemma of scientific man. The age of science and the social world. The repudiation of politics. The science of peace. The irrationality of scientific man. The moral blindness of scientific man. The tragedy of scientific man.